Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/imefm-05-2020-0226
|View full text |Cite
|
Sign up to set email alerts
|

Islamic banking efficiency literature (2000–2020): a bibliometric analysis and research front mapping

Abstract: Purpose This paper aims to present a citation-based bibliometric review of Islamic banking efficiency literature from 2000 until August 2020 for analyzing the content of the literature and mapping future research directions. Design/methodology/approach Using bibliometric citation analysis, this study reviews and examines a total of 278 documents from Web of Science (WoS) indexed sources coupled with content analysis. Findings The results identified that the growth of Islamic banking efficiency literature h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 60 publications
0
18
0
4
Order By: Relevance
“…For instance, Violeta and Gordana have employed bibliometric analysis to spot the trends of DEA application in banking [ 14 ]. Another study conducted by Ikra et al applied the bibliometric method to Islamic banking efficiency [ 15 ]. By an extensive search on the Scopus, Web of Science and Google Scholar, no such study was found related to bibliometric analysis on banking performance to the economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Violeta and Gordana have employed bibliometric analysis to spot the trends of DEA application in banking [ 14 ]. Another study conducted by Ikra et al applied the bibliometric method to Islamic banking efficiency [ 15 ]. By an extensive search on the Scopus, Web of Science and Google Scholar, no such study was found related to bibliometric analysis on banking performance to the economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Son yıllarda İ� slam iktisadı ve finansı alanında yayımlanan çalışmaların sayıları arttığı için bu alanda literatürün sayısal analizini yapan bibliyometrik çalışmaların sayısı artmaya başlamıştır. İ� slam iktisadı gibi daha genel bir başlık altında yapılan bibliyometrik çalışmalarının yanında (Handoko, 2020;O� zdemir ve Selçuk, 2021;Rusydiana, Sanrego ve Rahayu, 2021;Selçuk ve Yardımcıoğlu, 2017), İ� slami bankacılık (Biancone et al, 2020;İkra et al, 2021), tekafül (Khan et al, 2020;Nasir et al, 2021), sukuk (Paltrinieri et al, 2019;Rahman et al, 2020) gibi daha spesikfik konularda da çalışmalar görülmeye başlamıştır. Bu tür spesifik alanlardan biri de İ� slami mikrofinanstır.…”
Section: İslami Mikrofinans Literatürüunclassified
“…Bisnis perbankan tentu berbeda dengan industri lainnya. Perbankan sebagai perusahaan yang beroperasi di bidang keuangan mempunyai perbedaan variabel output dan input dari industri atau perusahaan yang beroperasi di sektor riil (Ikra et al, 2021;Yilmaz dan Güneş, 2015). Oleh sebab itu, pengukuran efisiensi perbankan perlu didahului dengan pengenalan variabel input dan output dalam aktivitas bisnisnya (Puteh et al, 2018).…”
Section: Telaah Pustakaunclassified